Hubungan Kepatuhan Obat Terhadap Indeks Glikemik Pada Pasien Usia Lanjut: Hubungan Kepatuhan Obat Terhadap Indeks Glikemik Pada Pasien Usia Lanjut - Sabiti, Farrah Bintang; Sa’dyah, Nur Anna Chalimah; Pranata, Meki; Tsalitsa, Mutiarani Nur (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2025)
Abstract: Diabetes mellitus is a chronic disease that can affect someone who is entering old age. Diabetes mellitus is characterized by excess fasting blood sugar values (≥126mg/dl) and HbA1C values ≥7%. A total of 147,734 cases of diabetes mellitus were found in Semarang city health centers. Medication adherence may be one of the factors in such high cases. With high medication adherence in elderly patients, it is expected that appropriate clinical outcomes will be achieved. The purpose of this study was to determine the relationship between sociodemographics and compliance with the use of diabetes mellitus drugs in elderly patients. This study is an analytical observational study conducted with a cross section study approach. This study was conducted at Halmahera Health Center and Gayamsari Health Center. This study used the chi square test which obtained a p value <0.05 which concluded that there was a relationship between sociodemographics and compliance with the use of diabetes mellitus drugs in elderly patients. This study can be concluded that there is a relationship between sociodemographics and compliance with the use of diabetes mellitus drugs in elderly patients